The Influence of Financial Literacy, Lifestyle, and Financial Inclusion on the Financial Management of Catholic Youth (OMK) of the Diocese of Maumere with Locus of Control as Moderation - Wangge, Patrisius Raymond; Kusuma, Putu Sri Arta Jaya (International Journal Labs, 2024)
This study aims to analyze the influence of financial literacy, lifestyle, and financial inclusion on the financial management of Catholic Young People (OMK) of the Diocese of Maumere, with the locus of control as a moderation variable. Using a quantitative method with an associative approach, data was collected through a questionnaire from 335 OMK respondents spread across 41 parishes in the Diocese of Maumere. The data was analyzed using Smart-PLS version 3. The results showed that financial literacy and financial inclusion had a significant positive effect on financial management, while lifestyle had a significant negative influence. Locus of control has been proven to strengthen the positive influence of financial literacy and financial inclusion, as well as weaken the negative influence of lifestyle on financial management. This study concludes that financial literacy, financial inclusion, and locus of control are important factors that support more optimal financial management among OMK, while consumptive lifestyle is a challenge that needs to be overcome. Practical implications of this study include providing guidance to OMK and pastoral ministers to improve financial management skills, as well as recommendations for policymakers to improve financial literacy and access to financial services for young people.